Cardiovascular rhythms in the 0.15-Hz band: common origin of identical phenomena in man and dog in the reticular formation of the brain stem? - ÇOTUK, HASAN BİROL (SPRINGER, 2004)
Selected examples from experiments in humans and dogs with time series of reticular neurons, respiration, arterial blood pressure and cutaneous forehead blood content fluctuations were analysed using multiscaled time-frequency distribution, post-event-scan and pointwise transinformation. We found in both experiments a 0.15-Hz rhythm exhibiting periods of spindle waves (increasing and decreasing amplitudes), phase synchronized with respiration at 1:2 and 1: 1 integer number ratios. At times of wave-epochs and n:m phase synchronization, the 0.15-Hz rhythm appeared in heart rate and arterial blood pressure. As phase synchronization of the 0.15-Hz rhythm with respiration was established at a 1:1 integer number ratio, all cardiovascular-respiratory oscillations were synchronized at 0.15 Hz. Analysis of a canine experiment supplied evidence that the emergence of the 0.15-Hz rhythm and n:m phase synchronization appears to result from a decline in the level of the general activity of the organism associated with a decline in the level of activity of reticular neurons in the lower brainstem network. These findings corroborate the notion of the 0.15-Hz rhythm as a marker of the trophotropic mode of operation first introduced by W.R. Hess.
Keywords: vegetative rhythms; cardiovascular-respiratory coordination; n : m phase synchronization; autogenic training; lower brainstem dynamics; nonlinear analysis; TIME-SERIES ANALYSIS; SKIN BLOOD-FLOW; SOMATOMOTOR FUNCTIONS; NEIGHBORING NEURONS; DISCHARGE PATTERNS; CUTANEOUS MICROCIRCULATION; SYMPATHOVAGAL BALANCE; CRITICAL-APPRAISAL; NERVOUS-SYSTEM; LASER-DOPPLER